“Hostbusters”: The Bacterial Endosymbiont Wolbachia of the Parasitoid Wasp Habrobracon hebetor Improves Its Ability to Parasitize Lepidopteran Hosts - Alsu M. Utkuzova; Ekaterina A. Chertkova; Natalia A. Kryukova; Julia M. Malysh; Yuri S. Tokarev (Insects)
Habrobracon hebetor is a globally acknowledged larval ectoparasitoid that is widely used to control lepidopteran pests. Wolbachia is a natural endosymbiont that regulates various aspects of the insect host biology. The ability of H. hebetor to paralyze and develop on lepidopteran larvae from five families was tested under laboratory conditions. Two lines of the wasp were used, “W+” containing a naturally occurring Wolbachia from the supergroup B, and “W−”, with the endosymbiont eradicated by antibiotic treatment, followed by propagation of 20 subsequent generations. The proportions of larvae in which host paralysis, as well as parasitoid oviposition, larval, pupal, and adult development were observed, were usually higher in W+ compared to W−. In Loxostege sticticalis, differences in these indices were not statistically significant. In Galleria mellonella, Mamestra brassicae, and Ostrinia nubilalis, some of the parasitism indices were significantly higher in W+ than in W−. In Bombyx mori and Plutella xylostella, H. hebetor could not complete its life cycle, but parasitism levels at the initial steps (from paralysis symptoms to the presence of larvae/pupae of the parasitoid) were 2–5 times lower in W− compared to W+ (p < 0.01). It can be suggested that the presence of Wolbachia is advantageous for H. hebetor, as it increases the success of parasitism in a broad range of lepidopteran hosts.